(untitled) (Revista de Ciências Agroveterinárias, 2017)
The granadilha is a sweet passion fruit, and the fruit is consumed while fresh. The method for seedling propagation is via sexual, but germination rates are low due to dormancy found in the seeds. The aim of the present study was to evaluate gibberellic acid and temperature in granadilha seed germination. The experimental design was completely randomized in a factorial 2 (temperature, 25 °C constant, and alternating 20-30 °C) x 2 (100 mg L-1 of gibberellic acid and absence), containing 5 replications and 80 seeds per repetition. They were evaluated every two days, until sixty days’ germination percentage, for germination speed index, germination velocity time, height (mm) and dry weight (mg) of seedlings. Best results were obtained for the granadilha seeds were found using 100 mg L-1 of GA3 and alternating temperatures of 20-30 °C. The highest percentage of granadilha seed germination was 53.2% at the temperature of 20-30 °C alternating.